(3GdJMa hGdgOGjGs - (3CHh HcQ eMeO,J (B380 (3g` s ((3jhSa Hf YHO Gddg GdOjQjfi s)
(3ChdgG (B:s
(3NUc Gddg HJMa EMSGfg , hefMc ef gOGjG EeJfGfg hHYO , aEfc , COGe Gddg YRc , CeQJfG dGRGd CeQc fGaPkG , hfgjc eWGYkG (B- (3Cf fNJGQ dc HYV eG bjd ai GdJMa hGdgOGjG s
(3BNQgG (B:s
(3hbGd ai Pdc CjVkG hdG CQJgG hLggG EdG Ydi XgQ GdWQb aCUHMJ NaJgG eaJhMI HdG WHb gPG BNQ eG GfJgi EdjfG eeG jJYdb HGdgOGjG Je GdcJGH HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B129s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 s
Keywords: (3GdJGQjNs